Case reportsLymphomas of the head and neck in dermatological practice - Sokołowska-Wojdyło, Małgorzata; Sikorska, Monika; Florek, Aleksandra; Drogoszewska, Barbara; Kowalczyk, Anna; Starzyńska, Anna; Szczerkowska-Dobosz, Aneta; Barańska-Rybak, Wioletta; Włodarkiewicz, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
The number of newly diagnosed cases of lymphomas of the head and neck region has been continually increasing over the recent years. The symptoms of these lymphomas are commonly similar to benign inflammatory diseases and thus frequently lead to clinical misdiagnoses. Many consultations, including dermatological one, and repeated tissue biopsies are often necessary because of the coexistence of necrosis and inflammation in the tumors. Biopsies should be deep enough – punch biopsies are not recommended. The classification of lymphomas has undergone dramatic changes with the increasing understanding and progress in immunohistochemistry and molecular biology. We describe five patients with lymphomas of oral and nasal cavities: 2 derived from B-cells, 2 from T-cells, and 1 from NK/T-cells. The initial presentation of these diseases often suggests an inflammatory process, such as an odontogenic inflammation, sinusitis or benign inflammatory process.